2019
DOI: 10.1113/ep087899
|View full text |Cite
|
Sign up to set email alerts
|

No impact of acute hyperglycaemia on arterial stiffness in the early and late follicular phases of the menstrual cycle in young females

Abstract: Acute hyperglycaemia may result in transient increases in arterial stiffness. However, research in healthy premenopausal women is lacking, and the impact of menstrual phase [early follicular (EF; low oestrogen) and late follicular (LF; high oestrogen)] on vulnerability to acute hyperglycaemiainduced changes in arterial stiffness is unknown. We hypothesized that an acute hyperglycaemiainduced increase in arterial stiffness in the EF phase would be attenuated in the LF phase. Seventeen healthy, naturally menstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(148 reference statements)
1
3
0
Order By: Relevance
“…A fourth finding is that AH did not adversely affect cfPWV or PIFV. Our cfPWV result confirms findings from other studies demonstrating no cfPWV response to AH in healthy humans (Kobayashi et al 2015;Williams et al 2020). PIFV, which principally reflects resistance arteriolar tone, was also not impaired by AH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A fourth finding is that AH did not adversely affect cfPWV or PIFV. Our cfPWV result confirms findings from other studies demonstrating no cfPWV response to AH in healthy humans (Kobayashi et al 2015;Williams et al 2020). PIFV, which principally reflects resistance arteriolar tone, was also not impaired by AH.…”
Section: Discussionsupporting
confidence: 91%
“…2015; Williams et al . 2020). PIFV, which principally reflects resistance arteriolar tone, was also not impaired by AH.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that global PWV significantly increased in both trials (0.29 m•s -1 , p < 0.001), driven by increases in brachial-femoral and femoral-ankle PWV (0.36 and 0.55 m•s -1 respectively) with no condition (p = 0.99) or interaction (p = 0.95) effect. Given the findings of Williams et al, [304], the mixed sample of Kelsch et al, [60] (12 males, 6 females) may have influenced the results with females being less susceptible to hyperglycaemic increases in arterial stiffness, however, it is apparent from these findings that in a healthy population at least, hyperglycaemia induced by consumption of a high glycaemic index drink does not appear to augment sitting-induced dysfunction. Another factor to consider may be physical activity preceding the prolonged sitting trials.…”
Section: Glucose Metabolism and Prolonged Sittingmentioning
confidence: 83%
“…The observed metabolic dysfunction observed in response to prolonged sitting is particularly problematic as both hyperglycaemia and associated insulin resistance are associated with acute vascular dysfunction and oxidative stress. Additionally, acute hyperglycaemia has been associated with increased peripheral artery stiffness, as assessed by pulse wave velocity in men [301][302][303], however, this effect has not been shown in a female population [304]. One study has also shown an increase in cfPWV during hyperglycaemia [305], however, in contrast to similar studies, the aforementioned trial utilised a mixed meal (80 g carbohydrate, 12 g fat, 18 g protein) rather than the typically employed glucose drink (70 g carbohydrate).…”
Section: Glucose Metabolism and Prolonged Sittingmentioning
confidence: 98%